Recent Advances in Medical Treatment of Malignant Pleural Mesothelioma - Jie YANG; Fanming KONG (Chinese Journal of Lung Cancer)
Malignant pleural mesothelioma (MPM) is a highly aggressive malignancy originating from mesothelial cells of the pleura, primarily associated with asbestos exposure, and is often characterized by poor prognosis. Due to the lack of specific clinical manifestations in the early stages, the diagnosis of MPM presents a significant challenge, leading to most patients being diagnosed at an advanced stage, which limits the effectiveness of surgical treatment. Consequently, systemic therapies are commonly required. Although Pemetrexed in combination with Platinum-based chemotherapy remains the first-line standard treatment for unresectable MPM, its therapeutic efficacy is limited, and more effective treatment strategies are urgently needed. In recent years, immune checkpoint inhibitors have made significant progress in the treatment of MPM, markedly improving patient survival outcomes. With the increasing depth of molecular biological research on MPM, targeted therapies offer promising personalized treatment options. Additionally, the therapeutic potential of novel strategies such as cell therapy and oncolytic virus therapy is beginning to emerge. This review summarizes the latest advancements in the medical treatment of MPM and looks forward to future therapeutic directions, aiming to provide insights for clinical practice.